(untitled) (Journal of Economic Research & Business Administration, 2016)
The article considers the main indicators of innovation development of economy of Kazakhstan. The paper determined the positive trends of innovative development which includes the growth of innovative products and services, increasing the number of people employed in R&D, growth of innovation activity of domestic enterprises. It was identified negative aspects which include the reduction of the share of R&D expenditures in GDP, weak links among the business and the scientific sector, low salaries of researchers in the higher education sector. The innovative activity of domestic companies, despite significant growth in recent years, is still critically low. It was found that the threat of the development of the innovation system can be: the weakening of the scientific potential of the country in connection with the move of scientists and engineers of Kazakhstan in foreign countries («brain drain»); increased competition in the area of innovation from the developing countries; the lack of domestic production with high added value on the world markets. Opportunities for the development of innovative economy in Kazakhstan connected with the implementation of the program of industrialinnovative development of Kazakhstan for 20152019 years, as well as strengthening cooperation between the private sector and science, the growth of the market for highend products in the framework of integration processes.